Hydrazine treatment improves conductivity of bacterial cellulose/graphene nanocomposites obtained by a novel processing method - Ccorahua, R (2017)
A novel method to prepare BC nanocomposites reinforced with reduced graphene oxide (RGO) is reported. A simple hydrazine treatment is shown to in-situ reduce the graphene oxide (GO) incorporated to BC films while increasing their conductivity. Raman spectroscopy was used to confirm the presence of graphene and assess the effect of the hydrazine treatment on its structure. XRD tests revealed no changes on BC structure. We hypothesize that this treatment removes the hydroxyl and epoxy groups present on the reduced graphene and increases the content of nonoxygenated carbon. These changes account for the increase in conductivity of the BC-based films, which behaved as an insulating material before the hydrazine treatment and reach an average conductivity value of 12 S/m after such a treatment.